Generalized Proportional Integral Control for an Unmanned Quadrotor System. (7th July 2015) - Fernández-Caballero, Antonio; María Belmonte, Lidia; Morales, Rafael; Andrés Somolinos, José
In this article, a generalized proportional integral (GPI) control approach is presented for regulation and trajectory tracking problems in a nonlinear, multivariable quadrotor system model. In the feedback control law, no asymptotic observers or time discretizations are needed in the feedback loop. The GPI controller guarantees the asymptotically and exponentially stable behaviour of the controlled quadrotor position and orientation, as well as the possibilities of carrying out trajectory tracking tasks. The simulation results presented in the paper show that the proposed method exhibits very good stabilization and tracking performance in the presence of atmospheric disturbances and noise measurements.